A comparative study on the emulsifying and foaming aspects of Gleditsia caspica galactomannan (as a new source of hydrocolloid), fenugreek galactomannan, and xanthan gum mixtures. Issue 12 (12th October 2022) - Niknam, Rasoul; Mousavi, Mohammad; Kiani, Hossein
Abstract: Emulsifying and foaming aspects of samples containing three hydrocolloids ( Gleditsia caspica (GG) galactomannan, xanthan gum (XG), and fenugreek galactomannan (FG)) were comprehensively investigated. By elevating the concentration of biopolymers, the values of emulsifying capacity, emulsion stability, zeta potential, and foaming stability were significantly raised. Contrarily, the values of foaming capacity, z‐average, and PDI were reduced. Among the utilized hydrocolloids, the samples containing FG especially when blended with XG had higher emulsifying capacity and emulsion stability values in comparison with other samples. Also, samples containing XG had higher foaming capacity and those containing FG had higher foaming stability values compared with other samples. The samples containing FG had higher zeta potential and lower z‐average and PDI values compared with other samples. Due to the obtained results, Gleditsia galactomannan could be considered as stabilizing agent in food formulations. Novelty impact statement: Introducing new sources of hydrocolloids (in current research, galactomannan obtained from Gleditsia caspica seed) with appropriate emulsifying and foaming properties is known as vital issue for researchers in food industry. Also, using mixture of hydrocolloids especially when G. caspica galactomannan was used in formulation of emulsions resulted in improved emulsifying and foaming aspects particularly emulsifying capacity, emulsion stability, and foaming stability.